Renal Function Evolution and Hypoaldosteronism Risk After Unilateral Adrenalectomy for Primary Aldosteronism - Queiroz, Nara L.; Stumpf, Matheo A. M.; Souza, Victor C. M.; Maciel, Ana Alice W.; Fagundes, Gustavo F. C.; Okubo, Jessica; Srougi, Victor; Tanno, Fabio Y.; Chambo, Jose L.; Pereira, Maria Adelaide A.; Pio-Abreu, Andrea; Bortolotto, Luiz A.; Latronico, Ana Claudia; Barisson Villares Fragoso, Maria Candida; Drager, Luciano F.; Mendonça, Berenice B.; Almeida, Madson Q. (Hormone and Metabolic Research, 2024)
Few studies demonstrated a percentage decrease in the estimated glomerular filtration rate (eGFR) at a single time and the rate of hypoaldosteronism after adrenalectomy for primary aldosteronism (PA). Our aim was to investigate the evolution of renal function and the hypoaldosteronism risk after adrenalectomy for PA. Aldosterone, renin, eGFR, and electrolyte levels were determined before and at 1 week, 1, 3 and 6 months after unilateral adrenalectomy in 94 PA patients (40 men and 54 women). The main outcome was the postoperative eGFR decline using analysis of covariance with the preoperative eGFR as a covariate. eGFR decreased during first postoperative week compared to 3 months before surgery. During the first 6 months, eGFR remained stable at similar levels to the first week after surgery. Age (p=0.001), aldosterone levels (p=0.021) and eGFR 3 months before surgery (p+<+0.0001) had a significant correlation with eGFR during first postoperative week. High aldosterone levels at diagnosis were correlated with decline in renal function in the univariate model (p=0.033). In the multivariate analysis, aldosterone levels at diagnosis had a tendency to be an independent predictor of renal function after surgery (p=0.059). Postoperative biochemical hypoaldosteronism was diagnosed in 48% of the cases after adrenalectomy, but prolonged hyperkalemia occurred in only 4 cases (4.5%). Our findings showed a decrease of eGFR after unilateral adrenalectomy for PA. Additionally, aldosterone levels at diagnosis correlated with postoperative renal function. Postoperative biochemical hypoaldosteronism occurred in almost half of the patients, but prolonged hyperkalemia with fludrocortisone replacement was less frequent.
Keywords: renal function; primary aldosteronism; adrenalectomy; hypoaldosteronism